2015
DOI: 10.1016/j.quageo.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Blake Event recorded near the Eemian type locality – A diachronic onset of the Eemian in Europe

Abstract: a b s t r a c tMultidisciplinary analysis including paleomagnetic, sedimentologic, sea-level change, luminescence dating and palynologic research was performed on a 25 m long orientated core taken at Rutten, close to Eemian key localities in the Netherlands. The main goal of our research was to test a possible delayed onset of temperate conditions in this region compared to Southern Europe, occurring within the Last Interglacial. The sediments revealed the presence of the paleomagnetic Blake Event in ca. 10 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 80 publications
(127 reference statements)
1
47
0
Order By: Relevance
“…These authors concluded that it began~121.5 ka and lasted to at least 113.5 ka. The results presented by Sier et al (2015) suggest that the start of the Eemian interglacial climatic event was delayed by 5000 years in northwest Europe compared to that in southern Europe e a point originally proposed by Kukla et al (2002). The latter authors suggested that the Eemian Stage interglacial in western Europe lasted for 17,000 or even 23,000 yr based on comparison of the marine and southern European terrestrial biostratigraphies.…”
Section: Northern European Versus North American Last Interglacial Rementioning
confidence: 72%
See 3 more Smart Citations
“…These authors concluded that it began~121.5 ka and lasted to at least 113.5 ka. The results presented by Sier et al (2015) suggest that the start of the Eemian interglacial climatic event was delayed by 5000 years in northwest Europe compared to that in southern Europe e a point originally proposed by Kukla et al (2002). The latter authors suggested that the Eemian Stage interglacial in western Europe lasted for 17,000 or even 23,000 yr based on comparison of the marine and southern European terrestrial biostratigraphies.…”
Section: Northern European Versus North American Last Interglacial Rementioning
confidence: 72%
“…They have arisen following detailed paleomagnetic studies by Sier et al (2011Sier et al ( , 2015 and that have identified and compared the palaeomagnetic Blake Event at sites in northwestern, central, and southern Europe. This event can be applied as a chronostratigraphic marker for comparison of records from marine and terrestrial sequences, and between high and low latitudes, although published durations vary from~1 kyr to more than 7 kyr.…”
Section: Northern European Versus North American Last Interglacial Rementioning
confidence: 99%
See 2 more Smart Citations
“…The top of this unit gradually changes to medium-and fine-grained sands. During the Eemian interglacial, between 122,000 and 115,000 years ago (Sier et al, 2015), an estuary developed within the former valley system (Figs 1A, 2C). The Eem Formation contains both clay and peat layers.…”
Section: Fig 1 Transect Through the Geological Models From Oosterwmentioning
confidence: 99%